Relationship Between Human Resource Management and Job Satisfaction Among Bank Employees: a Comparative Analysis of Public Sector and Private: Exploring the impact of HR practices on job satisfaction among bank employees (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In this paper we present about relationship between humanresource management and job satisfaction among bank employees: a comparativeanalysis of public sector and private. Job related outcomes are the mostimportant goals of HR function. Job happiness is an approach toward the job.Function of HR practices in the area of HR development: training, careergrowth, presentation and reward management, on job satisfaction.